Hunting for valuables from landfills and assessing their market opportunities A case study with Kudjape landfill in Estonia - Bhatnagar, Amit (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2017)
Landfill mining is an alternative technology that merges the ideas of material recycling and sustainable waste management. This paper reports a case study to estimate the value of landfilled materials and their respective market opportunities, based on a full-scale landfill mining project in Estonia. During the project, a dump site (Kudjape, Estonia) was excavated with the main objectives of extracting soil-like final cover material with the function of methane degradation. In total, about 57,777 m3 of waste was processed, particularly the uppermost 10-year layer of waste. Manual sorting was performed in four test pits to determine the detailed composition of wastes. 11,610 kg of waste was screened on site, resulting in fine (<40 mm) and coarse (>40 mm) fractions with the share of 54% and 46%, respectively. Some portion of the fine fraction was sieved further to obtain a very fine grained fraction of <10 mm and analyzed for its potential for metals recovery. The average chemical composition of the <10 mm soil-like fraction suggests that it offers opportunities for metal (Cr, Cu, Ni, Pb, and Zn) extraction and recovery. The findings from this study highlight the importance of implementing best available site-specific technologies for on-site separation up to 10 mm grain size, and the importance of developing and implementing innovative extraction methods for materials recovery from soil-like fractions